Effects of inclusion on the creep rate of piezoelectric films. Issue 4 (16th February 2019) - Li, H. B.; Li, Y. D.; Wang, X.
ABSTRACT: This paper presents an analytical method to study the effect of inclusions in piezoelectric materials on the creep rate. The driven force for the creep rate of piezoelectric materials with inclusion is from diffusional mass transport along the inclusion interface. The results show that the creep rate of piezoelectric materials containing the rigid inclusion with the shape parameter m = 0.8 appears at the minimum, and the effect of inclusion volume fraction on the creep rate of piezoelectric materials with soft inclusion becomes the smaller and smaller, as the stiffness of soft inclusion decreases. Thus, the effect of inclusion on creep characteristics can be improved by controlling the material property, the sizes, shapes, and volume ratio of inclusions.